The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/joa.12650
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage canals in the distal intermediate ridge of the tibia of fetuses and foals are surrounded by different types of collagen

Abstract: Some epiphyseal growth cartilage canals are surrounded by a ring of hypereosinophilic matrix consisting of collagen type I. Absence of the collagen type I ring may predispose canal vessels to failure and osteochondrosis, which can lead to fragments in joints (osteochondrosis dissecans). It is not known whether the ring develops in response to programming or biomechanical force. The distribution that may reveal the function of the ring has only been described in the distal femur of a limited number of foals. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Concomitant damage to the vessels (Tóth et al, 2013;Nissi et al, 2014;Tóth et al, 2015) would support our hypothesis that maximal joint excursions experienced for example during slipping and simulated in this ex vivo study, would cause high peak pressures in the femorotibial (FT) joint, biomechanically contributing to the development of OC lesions in pigs (Olstad et al, 2015;Hellings et al, 2017). Interestingly, De Koning et al (2014) found that a bedding of wood shavings at a relatively young age increases the odds for severe OC, similar to that observed in free ranged pigs (Etterlin et al, 2014(Etterlin et al, , 2015.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Concomitant damage to the vessels (Tóth et al, 2013;Nissi et al, 2014;Tóth et al, 2015) would support our hypothesis that maximal joint excursions experienced for example during slipping and simulated in this ex vivo study, would cause high peak pressures in the femorotibial (FT) joint, biomechanically contributing to the development of OC lesions in pigs (Olstad et al, 2015;Hellings et al, 2017). Interestingly, De Koning et al (2014) found that a bedding of wood shavings at a relatively young age increases the odds for severe OC, similar to that observed in free ranged pigs (Etterlin et al, 2014(Etterlin et al, , 2015.…”
Section: Discussionsupporting
confidence: 76%
“…Osteochondrosis (OC) in pigs develops after initial injury to the subchondral blood vessels, and leads via extracellular matrix thickening, lack of ossification of the necrotic cartilage, and splitting of the diseased cartilage with cracks, to loose cartilage flaps and fragments on the articular surface (Weisbrode, 2007;Olstad et al, 2015;Hellings et al, 2017). It has been estimated that around 80% of the pigs in today's porcine industry show superficial to mild signs of OC (Crenshaw, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In a review about cartilage cell clusters it was stated that “Such cell‐cell interactions are likely to also occur in cell clusters but this has not been formally demonstrated.” The current study gave further support to the existence of such connections. Cells with processes have been associated with progenitor characteristics and were also observed at the articular surface and in cartilage canals . Specific markers for progenitor cells were observed in chondrocyte clusters adjacent to severe cartilage degeneration .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, histopathological observations of the epiphyseal cartilage, particularly in foals, have shown that cartilage thickness, the number of vessels and their direction follow a heterogeneous distribution which could explain, in part, the susceptibility of specific sites within the joint to develop OC(D) [14][15][16]. However, processes leading to a vascular failure remain poorly elucidated and various hypotheses persist -specifically an implication of the forces (compression, shearing) exerted at the level of the osteochondral junction of the ossification front [1,12], extracellular matrix alteration [17,18], involvement of energetic metabolism [19,20], alteration of the chondrocyte proteome [21,22], hormonal dysregulation [23,24] and, in foals which suffered from bacterial infection during the first months of their lives, a process of septic ischemic chondronecrosis (9). Although the understanding of pathogenic processes leading to OC(D) has been the subject of much research, the dynamic aspect remain poorly studied.…”
Section: Introductionmentioning
confidence: 99%